Synthesis and characterization of graphene oxide-zirconia (GO-ZrO2) and hydroxyapatite-zirconia (HA-ZrO2) nano-fillers for resin-based composites for load-bearing applications. (February 2021) - Ilie, Nicoleta; Sarosi, Codruta; Rosu, Marcela-Corina; Moldovan, Marioara
Abstract: Objectives: The study aims to synthesize two different types of nano-fillers based on zirconia (ZrO2 ), which was functionalized with graphene oxide (GO-ZrO2 ), and hydroxyapatite (HA-ZrO2 ), and to implement them in an experimental methacrylate matrix containing new dimethacrylic oligomers. Methods: Nano-particles were synthesized via a modified Hummer's method and a sol-gel route. Bisphenol A-glycidyl methacrylate oligomers (Bis-GMA336[0–1] ) were synthesized from an epoxy resin that reacted with methacrylic acid in the presence of a basic catalyst. Traditional dental glass-fillers (Barium oxide/BaO and Barium fluoride/BaF2 ) were synthesized to create an experimental resin-based composite (RBC) used as reference. Filler morphology was evaluated via Transmission Electron Microscopy. RBCs were characterised by real-time Fourier transform infrared spectroscopy (degree of cure/DC, polymerisation kinetics), real-time spectrometry (light transmittance), 3-point bending test (flexural strength and modulus, Weibull parameters), and depth-sensing indentation test (plastic and elastic deformation parameters). Results: The synthesized nanohybrid fillers proved good dispersing performance. Mechanical properties and materials' reliability are within or above the mean values reported in the literature for RBCs. Addition of HA-ZrO2 -fillers resulted in a decrease light transmission, DC and mechanical properties. Except for the HA-ZrO2 RBC, materials showed a high resistance to softening in solvent. Conclusions: The synthesis of GO-ZrO2 and HA-ZrO2 nanohybrid particles and their implementation in experimental RBCs has proven successful. Adjustments of the light transmission through suitable co-fillers in addition to GO-ZrO2 as well as adjustments of the amount of HA-ZrO2 are necessary to enable reduced curing time (<20 s). Clinical significance: The addition of nanofillers with tailor-made properties can help improving the performance of modern restoratives.